Current developments on the application of microbial carotenoids as an alternative to synthetic pigments - Mussagy, Cassamo Ussemane [UNESP]; Khan, Sabir [UNESP]; Kot, Anna Maria (Taylor & Francis, 2021)
Microbial carotenoids have attracted rising interest from several industries as a sustainable alternative to substitute the synthetic ones. Traditionally, carotenoids available in the market are obtained by the chemical route using nonrenewable sources (petrochemicals), revealing the negative impact on the environment and consumers. The most promising developments in the upstream and downstream processes of microbial carotenoids are reviewed in this work. The use of agro-based raw materials for bioproduction, and alternative solvents such as biosolvents, deep eutectic solvents, and ionic liquids for the recovery/polishing of microbial carotenoids were also reviewed. The principal advances in the field, regarding the biorefinery and circular economy concepts, were also discussed for a better understanding of the current developments. This review provides comprehensive overview of the hot topics in the field besides an exhaustive analysis of the main advantages/drawbacks and opportunities regarding the implementation of microbial carotenoids in the market.
Keywords: Applications; carotenoids; extraction; market; microorganisms; production